AlergiaPT: A Portuguese media campaign to inspire people with allergies to make a positive change in their life. Issue 1 (8th March 2022) - Moreira, André; Mendes, Francisca de Castro; Rama, Tiago; Mota, Diogo; Silva, Diana; Pádua, Inês; Abreu, Cristina; Vasconcelos, Maria João; Farraia, Mariana; Paciência, Inês; Rufo, João; Barros, Renata; et al.
Abstract : Abstract: Allergic diseases comprise a significant cause of morbidity worldwide and a substantial burden on the health and medical systems of both developed and emerging economies. Although highly prevalent, relatively severe, and largely impactful on the quality of life of patients, allergic diseases are commonly trivialized. Increasing awareness of the relevance of allergic diseases as a major public health problem might lead to an improved acknowledgment by governments and health authorities. Based on the positive impact that media campaigns might have on health-related behaviors, as well as the large use of social media by different types of users, social media might be used as a powerful tool for spreading awareness and education even more effective than traditional face-to-face communication. Therefore, we aimed to develop a social media-based communication program, the AlergiaPT, reaching all stakeholders, to increase the awareness of allergic diseases tackling the causes, prevention, control, and economic impact. The AlergiaPT will provide user-generated and interactive content toward engagement, include both long-form and short-form video productions toward education, as well as stories and time-sensitive content toward empowerment. It will be targeted to all populations, engaging different stakeholders. Contents will address the 5 campaign goals: i) allergy health is promoted; ii) tolerance is actively reinforced, and avoidance reduced; iii) treatment control and guided self-management of patients of asthma, rhinitis, food allergy, and atopic eczema are strengthened; iv) recognition and treatment of severe allergy and anaphylaxis are improved, and v) indoor air quality is promoted. Engagement on the campaign will be promoted through stepwise educational takeaways meetings using different social media, and targeting all audience groups, by promoting the organization of resources for common goals and the involvement of social media to improve public awareness. The impact of AlergiaPT will be assessed through google analytics.